Eco Printing as an Environmentally Friendly Effort in Malaysia - Laili, Uliyatul; Rohmawati, Riska; Hasina, Siti Nur; Septianingrum, Yurike; Rahayu, Esty Puji (LP2M INSURI Ponorogo, 2024)
Eco print is not widely known by the wider community. Although this method, apart from being an effort to preserve nature, can also be used as a creative economic development. Therefore, this community service aims to provide skills training to Universiti Malaysia Kelantan students to be able to become entrepreneurs using Eco print techniques by utilizing the potential of leaf media. This community service activity was carried out at Nahdlatul Ulama University Surabaya, namely by providing prior education regarding Eco printing. Then, it was continued by providing training on Eco print making techniques which consisted of scouring, mordanting and finally scouring. The partners for this community service activity were 14 students from Unirversiti Malaysia Kelantan. The results of this community service show an increase in participants' knowledge regarding Eco print techniques. Before the counseling was carried out, some of the participants had less knowledge of 73%. After the Eco print counseling and training was carried out, almost all of the participants had good knowledge of 80%. This ecoprint counseling and training is hoped that students from Universiti Malaysia Kelantan can initiate an Eco print entrepreneurship development program in their country